The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1590/1809-43412016v13n1p155
|View full text |Cite
|
Sign up to set email alerts
|

Living longer: are we getting older or younger for longer?

Abstract: Since the second half of the 20th century survival has been democratised in most countries. More and more people reach an advanced age. The objective of this paper is to discuss how phases of the life cycle are being re-defined in the context of a world in transformation: the universalization of social security that guarantees income for older people; technological advances that have increased the velocity of communication and the demand for continuing education; medical advances; and changes in family organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Another study pointed out that the initiative to participate in the U3A was based on intrinsic reasons or dependent on the wishes of the elderly. Thus, the adherence of the elderly to these university programs is usually voluntary, considering their interests and needs 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study pointed out that the initiative to participate in the U3A was based on intrinsic reasons or dependent on the wishes of the elderly. Thus, the adherence of the elderly to these university programs is usually voluntary, considering their interests and needs 16 .…”
Section: Discussionmentioning
confidence: 99%
“…These are women who have studied more and entered the labor market 19 . Moreover, another study, which also identified a greater participation of the female sex in the U3A, found that the concepts considered important in the search for this form of education by the female public were the search for identity and the valorization of memory 16 .…”
Section: Discussionmentioning
confidence: 99%
“…A composição de um leque de possibilidades diversificadas de representações da aparência, envolvendo idosos acabava sendo dicotomizada, não incluindo, possivelmente, a totalidade das experiências de ser velho. Estudos subsequentes e mesmos os mais recentes sobre a dicotomização da apresentação pessoal e coletiva da velhice presentes no imaginário social mostraram, no entanto, que passados quase 15 anos a situação não se modificou muito (Laranjeira, 2010;Plens, Domingues, Batistoni, & Lopes, 2012;Piccoli, Lopes, Araújo, & Graeff, 2012;Silva, Cachioni, & Lopes, 2012;Camarano, 2016;Fin, Portella, & Scortegagna, 2017).…”
unclassified